2015
DOI: 10.1128/jb.02564-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Activity and Regulon of the Two-Component Regulatory System Composed by Cjj81176_1484 and Cjj81176_1483 of Campylobacter jejuni

Abstract: Campylobacter jejuni is a leading cause of bacterial diarrheal disease and a frequent commensal of the intestinal tract in poultry and other animals. For optimal growth and colonization of hosts, C. jejuni employs two-component regulatory systems (TCSs) to monitor environmental conditions and promote proper expression of specific genes. We analyzed the potential of C. jejuni Cjj81176_1484 (Cjj1484) and Cjj81176_1483 (Cjj1483) to encode proteins of a cognate TCS that influences expression of genes possibly impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…We showed by modelling that RacR activity decreases during the high to low oxygen shift and this can account for changes in expression of its major target genes, i.e., mfr, aspA, dcuA, cj0358 seen in this study. The signal for the Cj1491/Cj1492 system is unknown but this system seems mainly to regulate the gluconate dehydrogenase (cj0414/ 415) and possibly the c-type cytochrome cj0037c (cccC) genes (Luethy et al, 2015), both of which we identified as oxygen-regulated in this study. The Cj1492 response regulator was also approximately twofold higher in abundance at 40% versus 150% aerobiosis (Supporting Information Table S2).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We showed by modelling that RacR activity decreases during the high to low oxygen shift and this can account for changes in expression of its major target genes, i.e., mfr, aspA, dcuA, cj0358 seen in this study. The signal for the Cj1491/Cj1492 system is unknown but this system seems mainly to regulate the gluconate dehydrogenase (cj0414/ 415) and possibly the c-type cytochrome cj0037c (cccC) genes (Luethy et al, 2015), both of which we identified as oxygen-regulated in this study. The Cj1492 response regulator was also approximately twofold higher in abundance at 40% versus 150% aerobiosis (Supporting Information Table S2).…”
Section: Discussionmentioning
confidence: 83%
“…At least three regulatory systems are, however, known to affect expression of different electron transport genes in C. jejuni. These are the RacRS two-component system (van der Stel et al, 2015), the Cj1491/Cj1492 twocomponent system (Luethy et al, 2015) and the LysR family regulator Cj1000 (Dufour et al, 2013). Of these, RacRS is understood in most detail and responds to low oxygen in the presence of nitrate or TMAO to effectively repress fumarate transport and respiration genes (van der Stel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the CetB and CetC proteins, consisting of single PAS domains, and CetZ, consisting of two tandem PAS domains linked to a methyl-accepting chemotaxis domain are involved in energy and redox taxis (Hendrixson et al, 2001 ; Reuter and van Vliet, 2013 ). The Cj1491-92c two-component system has a PAS domain-containing histidine kinase, and controls expression of a gluconate dehydrogenase, and other proteins involved in heme or iron acquisition, and respiration (Luethy et al, 2015 ). Based on the Pfam classification of domains, all these PAS domains fall into the PAS9 family.…”
Section: Resultsmentioning
confidence: 99%
“…The Campylobacter genome encodes other environmental sensing modules, including those involved in chemotactic sensing (Marchant et al, 2002 ) and gene regulation (Raphael et al, 2005 ). Among the repertoire of sensing modules, PAS domains have been linked to both chemotaxis sensors (Reuter and van Vliet, 2013 ) and two-component sensors (Luethy et al, 2015 ). PAS (Per, Arnt, Sim) domains are wide-spread in bacteria, archea, and eukaryotes, and have roles in sensing a wide range of stimuli including light, oxygen, redox potential, and even play a role in circadian regulation in higher eukaryotes (Taylor and Zhulin, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 6 ). CJJ81176_1483 is part of a newly identified two-component system that regulates a gluconate dehydrogenase complex important for chick colonization 31 . These data represent 3 distinct genetic variations (PV, SNP, and MNV) in genes with diverse roles (chicken colonization, osmotic stress/house keeping, two-component system) and demonstrate the genetic adaptability of C. jejuni in vivo .…”
Section: Genome Variant Selection During Human Infectionmentioning
confidence: 99%